2-Amino-3-carboxypyrazin-1-ium perchlorate bis(2-aminopyrazin-1-ium-3-carboxylate) monohydrate - Berrah, Fadila (International Union of Crystallography, 2012)
The asymmetric unit of the title compound, C(5)H(6)N(3)O(2) (+)·ClO(4) (−)·2C(5)H(5)N(3)O(2)·H(2)O, comprises two symmetry-independent zwitterions, one cation, one perchlorate anion and one water molecule. In the crystal, the three different types of organic entities are linked by N—H⋯O and N—H⋯N hydrogen bonds, forming undulating sheets parallel to (1-10). These sheets are in turn connected by O—H⋯N and O—H⋯O hydrogen bonds involving perchlorate anions and water molecules, forming a three-dimensional network. Intramolecular N—H⋯O and weak intermolecular C—H⋯O hydrogen bonds are also present.